A lumped-element model of the chinchilla middle ear - Bowers, Peter (J Acoust Soc Am, 2019)
An air-conduction circuit model was developed for the chinchilla middle ear and cochlea. The lumped-element model is based on the classic Zwislocki model of the same structures in human. Model parameters were fit to various measurements of chinchilla middle-ear transfer functions and impedances, using a combination of error-minimization-driven computer-automated and manual fitting methods. The measurements used to fit the model comprise a newer, more-extensive data set than previously used, and include measurements of stapes velocity and inner-ear sound pressure within the vestibule and the scala tympani near the round window. The model is in agreement with studies of the effects of middle-ear cavity holes in experiments that require access to the middle-ear air space. The structure of the model allows easy addition of other sources of auditory stimulation, e.g., the multiple sources of bone-conducted sound—the long-term goal for the model's development—and mechanical stimulation of the ossicles and round window.